Fusing mobile phone data with other data sources to generate input OD matrices for transport models - Montero Mercadé, Lídia; Ros-Roca, Xavier; Herranz, Ricardo; Barceló Bugeda, Jaime (Elsevier, 2019)
OD matrices that describe mobility patterns provide major input to most transport analysis models. Since OD matrices are not yet directly observable, they are usually estimated indirectly. Data from new sources such as mobile phone records and GPS traces from mobile apps are emerging alternatives that allow for cheaper and timely estimates. However, they are still hindered by weaknesses that must be studied for use as input to transportation models. This paper presents a case study using mobility data from mobile phone records, with the goal of establishing a methodology for validating the obtained OD matrices and generating the appropriate input for traffic assignment models. Spatial and temporal consistency of OD data elaborated from mobile records has been proved to be useful for transportation modelling needs. Peer Reviewed